Inflammatory Biomarkers and Clinical Judgment in the Emergency Diagnosis of Urgent Abdominal Pain. (1st February 2019) - Breidthardt, Tobias; Brunner-Schaub, Nora; Balmelli, Catharina; Insenser, Juan Jose Sancho; Burri-Winkler, Katrin; Geigy, Nicolas; Mundorff, Lukas; Exadaktylos, Aristomenis; Scholz, Julia; Haaf, Philip; Hamel, Christian; Frey, Daniel; et al.
Abstract: BACKGROUND: The early diagnosis of urgent abdominal pain (UAP) is challenging. Most causes of UAP are associated with extensive inflammation. Therefore, we hypothesized that quantifying inflammation using interleukin-6 and/or procalcitonin would provide incremental value in the emergency diagnosis of UAP. METHODS: This was an investigator-initiated prospective, multicenter diagnostic study enrolling patients presenting to the emergency department (ED) with acute abdominal pain. Clinical judgment of the treating physician regarding the presence of UAP was quantified using a visual analog scale after initial clinical and physician-directed laboratory assessment, and again after imaging. Two independent specialists adjudicated the final diagnosis and the classification as UAP (life-threatening, needing urgent surgery and/or hospitalization for acute medical reasons) using all information including histology and follow-up. Interleukin-6 and procalcitonin were measured blinded in a central laboratory. RESULTS: UAP was adjudicated in 376 of 1038 (36%) patients. Diagnostic accuracy for UAP was higher for interleukin-6 [area under the ROC curve (AUC), 0.80; 95% CI, 0.77–0.82] vs procalcitonin (AUC, 0.65; 95% CI, 0.62–0.68) and clinical judgment (AUC, 0.69; 95% CI, 0.65–0.72; both P < 0.001). Combined assessment of interleukin-6 and clinical judgment increased the AUC at presentation to 0.83 (95% CI, 0.80–0.85) and after imaging to 0.87 (95% CI, 0.84–0.89) and improved the correct identification of patients with and without UAP (net improvement in mean predicted probability: presentation, +19%; after imaging, +15%; P < 0.001). Decision curve analysis documented incremental value across the full range of pretest probabilities. A clinical judgment/interleukin-6 algorithm ruled out UAP with a sensitivity of 97% and ruled in UAP with a specificity of 93%. CONCLUSIONS: Interleukin-6 significantly improves the early diagnosis of UAP in the ED.